RECENT ADVANCES IN DENTISTRY - A THEORETICAL REVIEW - Snehaa Baskaran; S. Preetha; Kavitha. S; Lavanya Prathap (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Thisarticle is about the recent advances in dentistry in all aspects. There have been many advancements that have made dental procedures very effective and cost less. Imaging technologies, Dental restorative materials, Dental implants, Paediatric dentistry, Operative dentistry, Preventive dentistry and Anesthesia dentistry are some fields in dentistry which has a lot of recent advancements. Dental materials have undergone a lot of advancements making it easier for the patient and long lasting. These advances have made the visit to the doctor pleasant. Dentists should educate the patients on how these advances would help them. Invisalign is the latest technology in dentistry. This is a clear alternative to metal braces which is transparent and helps you have a better smile.